P024 Plasma acetic acid, propanoic acid, and isobutyric acid are associated with treatment response in pouchitis patients treated with antibiotics. (25th January 2019) - Segal, J; Sarafian, M; Serrano Contreras, J I; Pechlivanis, A; Siaw, Y; Clark, S; Braz, L; Holmes, E; Hart, A
Abstract: Background: Restorative proctocolectomy is considered an option for patients with medically refractory ulcerative colitis. Short chain fatty acids (SCFA) are organic fatty acids with 1–6 carbons which arise from bacterial metabolism from carbohydrates entering the colon. In pouchitis, they have been found in significantly lower concentrations in faecal samples from patients with pouchitis when compared with healthy controls. The aim of the study was to measure SCFA in plasma in patients with pouchitis who were treated with antibiotics and compare levels of SCFA in those who responded to antibiotics vs. those who failed to respond to antibiotics. Methods: Pouchitis was defined using the pouch disease activity index (PDAI) and pouchitis was considered when the score was 7. Response to antibiotics was defined as either a 2-point reduction in PDAI or a score of <7. Patients were classified as off antibiotics if they had stopped all antibiotics for a period of at least 2 weeks prior to sample collection. Blood was centrifuged at 1, 600 g for 15 min. The plasma supernatant was then transferred into a 5 ml Eppendorf tube and snap frozen to be then stored at −80°C. Plasma SCFA were measured using an Agilent 7000C Triple Quadrupole GC/MS-MS System. Simca was used for multi-variate analysis and T-tests were used for univariate analysis. Results: There were 23 patients. Thirteen samples were on antibiotics and 10 samples were off antibiotics. The median age of the patients was 43 (21–64). Seven patients were on ciprofloxacin and metronidazole, four were on ciprofloxacin and two were on Augmentin. There were 9 patients that responded to treatment and 14 that did not respond to treatment. On multi-variate analysis, there were no significant differences between patients who responded to treatment and those that did not. There were also no significant differences between patients on and off antibiotics. On univariate sub-analysis of patients where samples were taken off antibiotics there were significant decreases in isobutyric acid 671507.8 µM vs. 727066.1 µM ( p < 0.03) and significant increases in acetic acid 6250801 µM vs. 376499 µM in responders vs. non responders ( p < 0.04). Conclusions: Our study highlighted that there were significant differences in plasma SCFAs that could differentiate between patients with pouchitis who were able to maintain clinical response vs. non-responders when antibiotic therapy was withdrawn. This study may therefore suggest that SCFA may play a role in the maintenance of remission from pouchitis.